Pengaruh Micro Teaching dan Efikasi Diri terhadap Kesiapan Mengikuti Pengenalan Lapangan Persekolahan (PLP) Mahasiswa Prodi Pendidikan Ekonomi Semester VIII Universitas Bhinneka PGRI Tulungagung - Sari, Oktafiya Bela; Subagyo, Siswo (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this study was to determine the effect of micro teaching and self-efficacy on the readiness to participate in the School Field Introduction (PLP) of students of the 8th semester of the Economics Education Study Program, Bhinneka PGRI University, Tulungagung. This study used quantitative research. The data collection method used a questionnaire with a sample of 92 respondents. The data analysis used in this study was multiple linear regression analysis. The results of this study indicate that: (1) there is a partial effect of micro teaching (X1) on the readiness to participate in PLP (Y) this is indicated by the t-count value (3.313) > t-table (1.987) and a significance value of 0.001 < 0.05, and self-efficacy (X2) on the readiness to participate in PLP (Y) this is indicated by the results of t-count (10.444) > t-table (1.987) and a significance value of 0.000 < 0.05. (2) there is a simultaneous influence of micro teaching (X1) and self-efficacy (X2) on readiness to participate in PLP (Y) this is proven by the results of f count (139.220) > f table (3.10) with a significance level of 0.000 < 0.05 (3) the results of multiple linear regression analysis obtained a linear equation, namely; Y = 13.975 + 0.224X1 + 0.638X2. and the magnitude of the influence of micro teaching and self-efficacy on readiness to participate in PLP (R2) is 75.2% and the remaining 24.8% is influenced by factors outside the variables. indicated by the calculated t value (3.313) > t table (1.987) and a significance value of 0.001 < 0.05, and self-efficacy (X2) on readiness to follow PLP (Y) this is indicated by the calculated t result (10.444) > t table (1.987) and a significance value of 0.000 < 0.05. (2) there is a simultaneous influence of micro teaching (X1) and self-efficacy (X2) on readiness to follow PLP (Y) this is proven by the calculated f result (139.220) > ft table (3.10) with a significance level of 0.000 < 0.05 (3) the results of multiple linear regression analysis obtained a linear equation, namely; Y = 13.975 + 0.224X1 + 0.638X2. and the magnitude of the influence of micro teaching and self-efficacy on readiness to participate in PLP (R2) was 75.2% and the remaining 24.8% was influenced by factors outside the variables.